Diversité des familles et bien-être en Suisse Enquêtes sur les familles et les générations 2013 et 2018 - Rossier, Clémentine; Bernardi, Laura; Sauvain-Dugerdil, Claudine (Terrains des sciences sociales, 2023)
A typical trajectory continues to dominate the life course in Switzerland: most people marry, have children, and adopt an unequal division of work between spouses. How can we understand this (relatively) weak diversity in family forms? Swiss institutions remain largely conceived in reference to the "Male Breadwinner" model: do individuals who do family in alternative ways encounter specific difficulties, which encourage conformity? Researchers from the National Centre for Competence in Research LIVES test this hypothesis with data from the families and generations Surveys collected in 2013 and 2018 by the Federal Statistical Office. Do parents who cohabit, are both fully employed, get separated, adopt shared custody, remain without children or have migrated, encounter economic, relational, or day-to-day management disadvantages which affect their health and life satisfaction?